SKEMA PEREKRUTAN MAHASISWA SEBAGAI TENAGA KERJA OUTSOURCING DALAM SEBUAH EVENT MICE (STUDI KASUS MAHASISWA POLITEKNIK NEGERI JAKARTA) - Yosi Erfinda (Journal of Tourism Destination and Attraction, 2019)
In Business activity company that moves in service industries event managemet / mice is depend one human resources in the field of event / mice. Many companies Professional Conference Organizer (PCO) / Professional Exhibition Organizer (PEO) / Destination Management Company (DMC) who recruited students of MICE in taste of Polytechnic Jakarta ( PNJ ) as outsourcing team in the event, it’s a good benefit for the company and students or pnj as institutions. However there are fundamental problem cant been seen at this time, where the system has no firm as search exists between resources and instiitutions as a human resources’s seeker. Based on the background, this research on a scheme the process of students as the power outsourcing work the mice into a thing that matters to do.This study aims to produce a system of labor outsourcing who controlled. In support of this research, and methods used in this study are: in-depth interview method and analysis of componential. Both in use for this method could describe data support in making the recruitment of a scheme to suit the needs of industry. The result of research is expected able to contribute to a system model recruitment suitable between the company pco / peo / dmc with institutions pnj in the future. Definitely that created a good system can be provide benefit which is balanced between the two sides.